Changes in biomechanical parameters under the feet while maintaining balance in basketball players before and after training - Vasilyev R. ,; Vasilyeva I.A. ,; Kovalev A.A. ,; Vodopyanov L.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determination of the nature of changes in the biomechanical parameters of the load under the foot and the postural status of basketball players under the influence of training. Methods and structure of the study. The experiment involved 28 athletes from women's and men's basketball teams of the first division of the Republic of Serbia. On the podometric platform «RSscan» (500Hz), the subjects performed two modified Romberg tests with eyes open and eyes closed. The measurement was taken immediately before and after training. The parameters of the trajectory of the displacement of the center of pressure, the speed of movement of the center of pressure, the pressure values ​​under the entire foot, as well as in the metatarsal and heel zones of both legs were recorded. Results and conclusions. Despite the training, the pressure in the heel zone relative to the metatarsal zone remained 10% higher. After training, in both tests, the trajectory of the center of pressure movement in men significantly decreased. The difference between men and women affected only the speed of movement of the center of pressure in the metatarsal zone of the feet, recorded after training. Basketball players of both sexes are characterized by a shift in the center of pressure predominantly in the medial-lateral direction.